1995
DOI: 10.2527/1995.73113358x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding fat and(or) milk products to the weanling pig diet on performance in the nursery and subsequent grow-finish stages

Abstract: Six experiments were conducted to evaluate the use of fat in diets containing a high level of milk products for weanling pigs. In Exp. 1, 192 pigs (6.6 kg and 23 d) were used to determine whether milk products (0 or 40%) in the diet influenced the utilization of fat (0 or 10%). No fat x milk product interactions were found. Adding milk products to the diet improved (P < .01) ADG, ADFI, and gain/feed (G/F). Adding fat to the diet did not influence performance. In Exp. 2, 3, and 4, 576 pigs (6.0 kg and 20 d) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
0
13

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 26 publications
7
28
0
13
Order By: Relevance
“…Additionally, dietary adjustment was aimed at maximizing production performance without regard to nutrient oversupply, namely protein and amino acids (Lee et al, 2001). However, several studies found that energy levels in the diets did not affect growth performance in weaned piglets (Tokach et al, 1995;Smith et al, 1999). Digestibility of CP at the terminal ileum was from 60% to 80% in weaning pigs fed a diet based on triticale and wheat (Hogberg & Lindberg, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, dietary adjustment was aimed at maximizing production performance without regard to nutrient oversupply, namely protein and amino acids (Lee et al, 2001). However, several studies found that energy levels in the diets did not affect growth performance in weaned piglets (Tokach et al, 1995;Smith et al, 1999). Digestibility of CP at the terminal ileum was from 60% to 80% in weaning pigs fed a diet based on triticale and wheat (Hogberg & Lindberg, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Em situação parecida, Mahan & Newton (1993) recomendaram inclusão entre 35 e 45% dos produtos lácteos. Neste estudo, os distintos resultados de desempenho foram semelhantes aos encontrados por Tokach et al (1995) nos primeiros 14 dias, quando determinaram os efeitos da adição de produtos lácteos (40%) em dietas para leitões desmamados aos 23 dias de idade.…”
Section: Resultsunclassified
“…Na tentativa de assegurar o desempenho satisfatório do leitão, minimizando os distúrbios digestivos do pós-desmame, vários autores têm estudado alternativas para melhorar as características das dietas fornecidas nos períodos afins, durante as fases de creche (Mahan & Newton, 1993;Mascarenhas et al, 1999;Trindade Neto et al, 1999).…”
Section: Introductionunclassified
See 2 more Smart Citations